Preservation of Retinal Function Through Synaptic Stabilization in Alzheimer's Disease Model Mouse Retina by Lycium Barbarum Extracts - Liu, Jinfeng; Baum, Larry; Yu, Shasha; Lin, Youhong; Xiong, Guoying; Chang, Raymond Chuen-Chung; So, Kwok Fai; Chiu, Kin (Frontiers in Aging Neuroscience, 2022)
In Alzheimer's disease (AD), amyloid β deposition-induced hippocampal synaptic dysfunction generally begins prior to neuronal degeneration and memory impairment. Lycium barbarum extracts (LBE) have been demonstrated to be neuroprotective in various animal models of neurodegeneration. In this study, we aimed to investigate the effects of LBE on the synapse loss in AD through the avenue of the retina in a triple transgenic mouse model of AD (3xTg-AD). We fed 3xTg-AD mice with low (200 mg/kg) or high (2 g/kg) dose hydrophilic LBE daily for 2 months from the starting age of 4- or 6-month-old. For those started at 6 month age, at 1 month (though not 2 months) after starting treatment, mice given high dose LBE showed a significant increase of a wave and b wave in scotopic ERG. After 2 months of treatment with high dose LBE, calpain-2, calpain-5, and the oxidative RNA marker 8-OHG were downregulated, and presynaptic densities in the inner plexiform layer but not the outer plexiform layer of the retina were significantly increased, suggesting the presynaptic structure of retina was preserved. Our results indicate that LBE feeding may preserve synapse stability in the retina of 3xTg-AD mice, probably by decreasing both oxidative stress and intracellular calcium influx. Thus, LBE might have potential as a neuroprotectant for AD through synapse preservation.